Numerical methods for engineers and scientists : - Gilat, Amos (Wiley, 2014)
Ideal for both students and professionals who would like to become more adept at numerical methods, Numerical Methods For Engineers and Scientists familiarizes you with: The mathematical background and fundamentals of numerical methods; Solving nonlinear equations; Solving a system of linear equations; Eigenvalues and Eigenvectors; Function approximation, curve fitting, and interpolation; Differentiation; Integration; First-order and higher-order ODEs; Initial and boundary value problems